Audit Fees and IAS/IFRS Adoption: Evidence from the Banking Industry. (16th December 2013) - Cameran, Mara; Perotti, Pietro
<x xml:space="preserve">Abstract</x> The adoption of International Accounting Standards/International Financial Reporting Standards (IAS/IFRS) has two opposite effects on audit fees: on the one hand, greater effort is required from auditors, which is likely to be reflected by higher fees; on the other hand, if IAS/IFRS improve the quality of financial reporting, expected liability costs could decrease and lower fees may be demanded. We consider a large sample of Italian banks and we examine the effect of IAS/IFRS adoption on audit fees. The results show that higher fees (19.29 per cent in real terms) are paid after the switch to the new standards. Using a standard earnings management model, we do not find support for the idea that financial reporting quality is affected by the adoption of IAS/IFRS. The observed increase in fees is positively associated with the presence of financial derivatives held for hedging purposes. This paper extends the findings of prior research on the effect of IAS/IFRS adoption on audit fees; contrary to prior contributions, our analysis concentrates on the banking industry. Furthermore, unlike prior works, we consider both listed and non‐listed firms.